2022
DOI: 10.1891/cn-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Using Hygge to Promote Wellness and Coping With a Chronic Illness

Abstract: Hygge is a Nordic practice and mindset of creating warmth and comfort from within to improve one's wellness. Hygge has not been explored well in the scientific literature, especially in the context of a chronic illness. This article describes the experiences of an adult woman with cystic fibrosis, a progressive, incurable genetic disease primarily affecting the respiratory and gastrointestinal tracts, as she uses hygge to cope with the daily challenges of her illness. She also uses hygge as a framework for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the wake of the COVID-19 pandemic, the stage was set for hygge, a lifestyle that embraced finding solace in the new normal of social isolation (Kurtz, 2020). Hygge is also being gradually incorporated into various communities facing chronic illness as a coping and self-care mechanism to promote well-being (Hobson, 2023;Ladores et al, 2022;Roth, 2017). Self-care encompasses a holistic approach to well-being, involving deliberate practices that address physical, emotional, and mental needs (Riegel et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the wake of the COVID-19 pandemic, the stage was set for hygge, a lifestyle that embraced finding solace in the new normal of social isolation (Kurtz, 2020). Hygge is also being gradually incorporated into various communities facing chronic illness as a coping and self-care mechanism to promote well-being (Hobson, 2023;Ladores et al, 2022;Roth, 2017). Self-care encompasses a holistic approach to well-being, involving deliberate practices that address physical, emotional, and mental needs (Riegel et al, 2012).…”
mentioning
confidence: 99%
“…The purpose of this qualitative study was to explore how adults with CF use hygge practices to promote wellness and cope with their progressive disease. The study was informed by the lived experience of a member of the CF community who found restoration and focus through the incorporation of hygge into her lifestyle (Ladores et al, 2022). To our knowledge, this is the first exploration of how individuals with CF use hygge practices in their daily lives.…”
mentioning
confidence: 99%